Reutilização de Modelos de Requisitos por Analogia: Experimentação e Conclusões - Zirbes, Sérgio Felipe (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1995: Anais do IX Simpósio Brasileiro de Engenharia de Software, 1995)
This paper presents the conceptual framework, the organization, realization and analysis of a requirements reuse experiment. The reuse of requirements models is investigated in two different methodologies: according to the structured methodology, the modeling process is based on the use of Data Flow Diagrams, in the Object Orientation paradigm, Object Diagrams are used for modeling purposes. The research was achieved with the cooperation of 114 students/analysts, resulting in 175 series of Data Flow Diagrams and 23 series of Object Diagrams. Proper statistical analysis were conducted with these samples, in order to clarify questions about requirements reuse.